Cu Concentration in Vegetable-Cultivated Soil: Comparison Between Open Fields and Protected Environments in Brazil - Odair J. Schmitt; Jerônimo L. Andriolo; Tadeu L. Tiecher; Lessandro De Conti; Cledimar R. Lourenzi; Renan Costa Beber Vieira; Douglas R. Kaiser; Carina Marchezan; Aparecida Miranda Corrêa; Isley C. Bicalho Silva; Tatiane Chassot; Mario S. Wolski; et al. (Horticulturae)
High copper (Cu) concentration in soils used for vegetable production is an agricultural, social and environmental issue. The excess of Cu in soil can cause toxicity in plants, reducing growth and yields. Moreover, Cu can also be absorbed and accumulated in edible organs, increasing risks for human health. This study aimed to compare Cu fractions in soils: (1) non-cultivated, natural soil (NC), (2) soils cultivated with open field crops (FCs) and (3) soils cultivated in controlled environments (CEs). The survey was carried out on 25 sites in Rio Grande do Sul (Southern Brazil), with each site containing the three types of soils described above. From these sites, the four with the highest soil Cu concentrations were selected to compare soluble (Cu-CaCl2), available (Cu-EDTA) and total (Cu-EPA) Cu. Both total and available soil Cu concentration in soil solution, in CE and FC areas were higher than in NC. At sites 23R1 (Oxisol) and 11R1 (Molisol) the soluble and available Cu content was higher in the FC environment than in CEs, and the same was observed for the total Cu content at sites 23R1 (Oxisol) and 9R1 (Molisol). Some FC soils showed total Cu concentrations higher than the limits established by Brazilian environmental legislation, being, as a consequence, potentially contaminated. Soil monitoring and cropping practices must be adopted to reduce the Cu content in soils of vegetable crops in this region.